Hardening corporate accountability in commodity supply chains under the European Union Deforestation Regulation - Laila Berning; Metodi Sotirov (Regulation & Governance, 2023)
The European Union (EU) has recently introduced the Deforestation Regulation to close regulatory gaps in the sustainability and legality of global forest and agricultural commodity supply chains. We analyze this regulatory policy change by drawing on accountability scholarship and institutionalist theories of regulation. Our results show that the Regulation aims to enhance corporate accountability mechanisms through mostly state-based hard regulation of commodity supply chains, reducing the role of market incentives and private regulation. This policy change is found to be the result of strategic policy-oriented learning from perceived accountability failures of existing soft market-based instruments, voluntary trade agreements, and experience with market-correcting EU timber legality trade rules in a politically favorable context. The institutionalization of new forest-risk commodity supply chain accountability norms in new EU trade rules would, by design, harden foreign corporate accountability for negative socio-environmental externalities. However, the de-facto hardening will depend on the final regulatory design, acceptance, compliance, implementation, enforcement improvements, and avoidance of leakage effects.
Keywords: 330; EU policy; foreign corporate accountability; supply chain regulation; timber and agricultural commodities; zero-deforestation